Memory frictions and reconciliation: Neo-victorian gothic and gender violence in Katy Darby’s The Whores’ Asylum (2012) - Romero-Ruiz, María Isabel (My University, 2015)
Katy Derby’s first novel, The Whores’ Asylum (2012), is an attempt to deal with the issue of prostitution and rescue work in Oxford in the 1880s. Jericho is an area where, away from the prestigious university colleges, drunkards, thieves and prostitutes loiter around in depraved houses of accommodation and taverns. The protagonists, Stephen Chapman –a brilliant medical student --, Edward Fraser –a Theology student –, and Diana – the woman who runs a refuge for fallen women – are the three angles of a triangle where friendship, desire and secrets meet at the heart of Victorian England. A succession of dreadful events together with the violence exerted against women brings to light the context in which the helplessness of the innocent victims of lust and debauchery is shown. Their aim is not only to keep order in this working-class suburb, but also to find the way to show sympathy for the deaths and suffering of the “prostituted other”. At the same time Darby makes use of the Neo-Victorian Gothic to recover aspects of the Victorian archive which provide the setting to discuss issues of morality, sexual exploitation and reform so important for the Victorian mind but also of relevance in our contemporary societies. The role of medical practice and rescue work is emphasized from the very beginning, and allusions to many events and cultural aspects of the period are frequent, following the Neo-Victorian trend of re-writing the past. Similarly, the novel’s commitment to the memoir style represents an attempt at the restoration of justice for those neglected by past and present communities and whose suffering does not deserve any political consideration. Following Judith Butler’s theories of gender, violence and mourning, this paper aims to discuss issues of the Victorian neglected other and contemporary concerns about the deaths and suffering of the victims of sexual exploitation. As a consequence of humanity having been denied to particular groups of people both in the Victorian past and in our postmodern presents, violence has been justified against these marginalized groups that do not deserve mourning because of sexual, racial, religious or ethnic differences. In this context, the lives and deaths of prostitutes have no value or social relevance in the power regimes of the past and the present, perpetuating western systems of government and sovereignty across time and different locations.
Keywords: Darby, Katy. The Whores Asylum - Crítica e interpretación; Neo-victorian; Memory; Reconciliation; Gender violence; Gothic